Advancing Styrofoam Waste Recycling Management within the Framework of a Green Economy At UD Tiga Putra - Gatot Setyono; Rodhiyah; Ulum, Miftahul; Haryadi Ogsa, Muhammad Al Khawarizmi; Aditya, Bagas (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The increasing accumulation of Styrofoam waste has become a serious environmental concern due to its non-biodegradable properties and the lack of effective disposal and recycling pathways. Micro- and small-scale enterprises play a strategic role in addressing this issue at the local level, including UD Tiga Putra in Gresik, Indonesia, which is actively involved in Styrofoam waste processing. Before the implementation of this community engagement program, the enterprise encountered several operational challenges, such as the use of outdated processing equipment, limited production capacity, and inadequate managerial and occupational safety practices. In particular, the existing Styrofoam melting machine, with a capacity of 150 kg per day, frequently experienced technical failures and resulted in recycled products of inconsistent quality. To address these constraints, a community partnership program was developed by integrating technological upgrading, occupational health and safety improvement, and managerial capacity strengthening. A newly designed appropriate-technology Styrofoam melting machine with a capacity of 300 kg per day was introduced, leading to a substantial increase in production efficiency and operational stability. This technological enhancement was complemented by structured training on workplace safety, including the proper use of fire extinguishers and personal protective equipment, as well as mentoring on systematic financial record-keeping practices. The program outcomes indicate improved operational reliability, enhanced safety awareness among workers, and greater financial transparency. Overall, the findings demonstrate that an integrated, community-based approach can effectively enhance the resilience and competitiveness of small recycling enterprises while supporting circular economy initiatives and sustainable local economic development.